1997
DOI: 10.1542/peds.100.2.228
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Incontinence and Urinary Tract Infection and Their Resolution With Treatment of Chronic Constipation of Childhood

Abstract: Urinary symptoms were found in a significant number of children who had functional constipation and encopresis. With treatment of the constipation, most patients became clean and dry and further recurrence of urinary tract infections was prevented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
169
4
14

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 425 publications
(195 citation statements)
references
References 28 publications
8
169
4
14
Order By: Relevance
“…15 In addition, neurogenic bladder, intermittent catheterization and vesicoureteral reflux are major contributors to urinary tract infections for CP patients. 16 Karaman MI et al showed that neurogenic detrusor overactivity or dyssynergia (involuntary contractions during bladder filling) with a low bladder capacity was present in 21 CP children (58%).…”
Section: Discussionmentioning
confidence: 99%
“…15 In addition, neurogenic bladder, intermittent catheterization and vesicoureteral reflux are major contributors to urinary tract infections for CP patients. 16 Karaman MI et al showed that neurogenic detrusor overactivity or dyssynergia (involuntary contractions during bladder filling) with a low bladder capacity was present in 21 CP children (58%).…”
Section: Discussionmentioning
confidence: 99%
“…AEM hastalarında başvuru yakınmaları gündüz idrar kaçırma, ani sıkışma hissi (urgency), küçük miktarlarda sık sık işeme, yatak ıslatma ve idrar yolu infeksiyonudur. AEM'li çocukların %90'ında aynı zamanda KFK' da eşlik eder (27) . Gündüz inkontinansı olan pek çok çocuğun idrar tutma manevralarını kullanarak işemeyi geciktirmeyi alışkanlık hâline getirdikleri aileleri tarafından belirtilir.…”
Section: Discussionunclassified
“…Birkaç yazar KFK tedavisinin mesane semptomlarını düzelttiğini gösteren çalışmalar yapmışsa da bu konunun temel karakteristikleri ortaya konmamıştır (9,13,14) . O'Regan rektal manometri ile tanı koyduğu 22 hastanın tamamında detrussor instabilitesi saptamış KFK'sı iyileşen 17 hastanın 14'ünde (%82) tam düzelme 3 hastada (%18) kısmi düzelme sağlan-dığını bildirmiştir (6) .…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Many children do not experience the school toilets as safe or clean [6,7]. In some children avoidance of going to the toilet at school negatively affects health, with possible resultant consequences such as bladder dysfunction, urinary tract infections, constipation and psycho-social problems [4,[8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%